Band gap tunning to enhance photovoltaic response in NaNbO3-based bulk ferroelectrics. (December 2022) - Wang, Jitong; Peng, Zhanhui; Wang, Jicheng; Wu, Di; Yang, Zupei; Chao, Xiaolian
Abstract: The observation of anomalous photovoltaic effect and switchable photocurrent in ferroelectrics receive extensive attention for its great advantages in next-generation high-performance photovoltaic devices, but the key factor, the wide band gap results in low photocurrent output and photoelectric conversion efficiency. Focusing on narrowing band gap to improve photovoltaic performance in NaNbO3, in this work, we fabricated the NaNbO3 and 0.8NaNbO3 -0.2La(Mn0.5 Ni0.5 )O3 (abbreviated as 0.2NLMNO) ferroelectric ceramics through a solid state method. The optical absorption spectra reveal the band gap of ceramics reduce from 3.42 eV to 2.11 eV and the light absorption in visible region is significantly enhanced. A higher symmetry of crystal structure and great reduced resistance of grain and grain boundary induced by introducing La(Mn0.5 Ni0.5 )O3 . What's more, the photocurrent density of 0.2NLMNO improves approximately 10 times larger than that of pure ferroelectric NaNbO3, it is expected to explore a new ferroelectric material with photovoltaic effect. Graphical abstract: Fig. Band gap tunning to enhance photovoltaic response in NaNbO3 -based bulk ferroelectrics Image, graphical abstract